'Re-PEGing': an endoscopic approach to inadvertent early removal of PEG tube. Issue 3 (3rd May 2020) - Soliman, Youssef; Kurchin, Alexander; Devgun, Surinder
ABSTRACT: Inadvertent removal of percutaneous endoscopic gastrostomy (PEG) tube shortly after placement creates the potential for gastric perforation and requires immediate attention. This problem has been addressed in the past with either observation or surgery. We describe our experience with the alternative approach of semi-urgent 're-PEGing'. Our results in seven patients were favorable.